Sobre la presencia de Sternbergia lutea (L.) Ker-Gawler (Amaryllidaceae) en Extremadura. - Chaves, Antonio; López, Josefa; Devesa, Juan Antonio (Acta Botanica Malacitana, 2002)
On the presence of Sternbergia iutea (L.) Ker-Gawler (Amaryllidaceae) in Extremadura. Palabras clave. Sternbergia, Amaryllidaceae, corología, Extremadura, España. Key words. Stern bergia, Amaryllidaceae, chorology, Extremadura, Spain.